"Getting off the Tiger": The Spanish Transitional Model and its Influence on the Democratic Transitions in Argentina and Chile, 1977–1990. Issue 3 (3rd July 2019) - Kressel, Daniel Gunnar
Abstract : The article explains how the Spanish transition from dictatorship to democracy, as a "model" for a political reform devoid of transitional justice, informed the Argentine and Chilean democratic transition of the 1980s. It indicates that during the mid-1980s, Spanish figures promoted Spain's "pacted transition" in Latin America within particular intellectual networks. While ultimately failing to impact the Argentine democratisation, the Spanish discourse of "consensus" made a more salient impact in Chile during the late 1980s. The goal of this article is ultimately to suggest that while Chilean reformers designed their transitional model building on both the Spanish and Argentine precedents, their discourse bore a strong consistency with the core principles of the Spanish political reform, a fact that should be attributed to a decade of Chilean-Spanish dialogue.